ANALISIS KEUNTUNGAN USAHATANI PADI SAWAH ORGANIK DI KECAMATAN MUARA BULIAN KABUPATEN BATANG HARI (Studi Kasus di Desa Pasar Terusan) - Edison; Salina; Kernalis, Emy (Jurnal Ilmiah Sosio-Ekonomika Bisnis, 2019)
This research is to know: (1) the amount of profits earned by farmer from organic ricein Pasar Terusan village Muara Bulian district Batang Hari regency (2) the factors affecting the profits of the organic rice famers inPasar Terusan village Muara Bulian district Batang Hari regency. Data collected in this research is analyzed this data analize used methode used in quantitative descriptive method That is the advantage analysis consists of an analysis of the revenue and production costs for organic rice farming. To analyze the factors that affect the benefits of farming the organic rice used Multiple Linear regression analysis method. This research located in Pasar Terusan village Muara Bulian district Batang Hari regency in 01 October 2015 untill 01 November 2015. The results of this research indicate (1) the average profits of farming of organic rice in the area of research is Rp. 17.023.361/the planting season and the average profits of farming the organic rice per hectare in areas of research of Rp. 22.182.569/ha/year (2) Factors of land area, the cost of seed, the cost of drugs, and the cost of labor is influential in the real profits of farming the organic rice so well for enhanced. While the cost of fertilizer has no effect in the real profits of farming of organic rice, this is because the farmer have issued charges exceed the optimal range. From this research the expectation elucidation into the farm rice organic that knowledge acquire the biggest on farm application.